World Humanitarian Data and Trends 2018 - Nations Unies (United Nations, 2018)
World Humanitarian Data and Trends is an annual OCHA publication, which highlights major trends in the nature of humanitarian crises, their underlying causes and drivers, and the actors that participate in crises prevention, response and recovery. Beyond providing statistics, the report uses infographics to display trend analyses that show how the humanitarian landscape is evolving and how the humanitarian system can be more effective in a rapidly changing world. Data used in the report comes from a variety of sources and partners. The report is structured in three main sections: ‘the year in review’, which provides an overview of the humanitarian landscape in terms of funding, capacity, crises and appeals, a ‘regional perspectives’ section and ‘trends, challenges and opportunities’, which provides case studies on issues that impact humanitarian operations. The report is anchored in the Agenda for Humanity, launched at the World Humanitarian Summit held in May 2016. Highlights for 2018 include new case studies on protracted crises – the length of international response, the distribution of funding and people targeted for aid over time – as well as case studies on using artificial intelligence to track displacement, supporting local action through country-based pooled funds and attacks on education and healthcare facilities. The report aims to provide a “one-stop” shop for policy makers, researchers and humanitarian practitioners to have an evidence-base and advocacy tools for humanitarian assistance. This report is one part of OCHA’s efforts to improve data and analysis on humanitarian situations worldwide.